2019
DOI: 10.1186/s12943-019-1089-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of hypoxia in cancer therapy by regulating the tumor microenvironment

Abstract: AimClinical resistance is a complex phenomenon in major human cancers involving multifactorial mechanisms, and hypoxia is one of the key components that affect the cellular expression program and lead to therapy resistance. The present study aimed to summarize the role of hypoxia in cancer therapy by regulating the tumor microenvironment (TME) and to highlight the potential of hypoxia-targeted therapy.MethodsRelevant published studies were retrieved from PubMed, Web of Science, and Embase using keywords such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
988
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,315 publications
(1,087 citation statements)
references
References 128 publications
14
988
1
5
Order By: Relevance
“…462 The molecular mechanisms of anti-cancer drug resistance are also associated with tumor metabolism, the TME and CSCs, such as increasing drug metabolism and degradation of drug target proteins, enhance the tolerability of stressful TME conditions, and enhance the DNA damage response and antiapoptotic mechanisms of CSCs. 461,[463][464][465][466] Thus, to improve therapeutic effects, a multitargeted combination treatment is proposed for UPS inhibitors.…”
Section: Targeting E3 Enzymesmentioning
confidence: 99%
“…462 The molecular mechanisms of anti-cancer drug resistance are also associated with tumor metabolism, the TME and CSCs, such as increasing drug metabolism and degradation of drug target proteins, enhance the tolerability of stressful TME conditions, and enhance the DNA damage response and antiapoptotic mechanisms of CSCs. 461,[463][464][465][466] Thus, to improve therapeutic effects, a multitargeted combination treatment is proposed for UPS inhibitors.…”
Section: Targeting E3 Enzymesmentioning
confidence: 99%
“…It was clearly shown that the hypoxia condition affects the gene expression 21 . Numerous studies have demonstrated that the hypoxia microenvironment in the solid tumor contributes to cancer development and progression 6,14,22,23 . The chromatin structure plays an important role in controlling gene expression 24 .…”
Section: Discussionmentioning
confidence: 99%
“…To be able to grow and spread, lymphoma cells must learn how to overcome stress-induced by hypoxia, acidosis, increased levels of reactive oxygen species (ROS), and lack of nutrients. Hypoxia belongs to widely recognized factors that in a very complex fashion facilitate tumor cell survival and chemoresistance in all types of malignant diseases [75]. Hypoxia-inducible factors (HIFs) play a central role in the string of adaptation phenotypic changes associated with hypoxia, both in lymphoma cells and non-malignant cells of the tumor microenvironment [76].…”
Section: Hypoxia-induced Changes and Metabolic Reprogrammingmentioning
confidence: 99%